Selective p38MAPK isoform expression and activation in antineutrophil cytoplasmatic antibody-associated crescentic glomerulonephritis: role of p38MAPKα. Issue 5 (17th August 2007) - Polzer, K; Soleiman, A; Baum, W; Axmann, R; Distler, J; Redlich, K; Kilian, A; Krönke, G; Schett, G; Zwerina, J
Abstract : Objective: Crescentic glomerulonephritis (crGN) is a frequent and life-threatening manifestation of antineutrophil cytoplasmatic antibody-associated vasculitis. Up-regulation of proinflammatory cytokines contributes to renal damage by activation of p38 mitogen-activated protein kinases (MAPKs). However, it is unclear which of the four p38MAPK isoforms are expressed, activated and hence of major importance in crGN. Methods: Kidney biopsies of patients with antineutrophil cytoplasmatic antibody-positive crGN and control samples were investigated for the expression and phosphorylation of p38MAPK isoforms and downstream target kinase MAPKAP2 by immunohistochemistry. Expression and functional activation of p38MAPK isoforms by TNF was also assessed in a human podocyte cell line by reverse transcription–polymerase chain reaction, immunoblotting and kinase array. Results: Strong expression of p38MAPKα, β and γ isoforms was found in glomerular podocytes and crescents. Infiltrating leucocytes showed predominant p38MAPKα expression. Activation of p38MAPK and its downstream mediator MAPKAP2 was found in crGN confined to glomerular podocytes, crescents and inflammatory infiltrates. Interestingly, corticosteroid treatment before kidney biopsy diminished p38MAPK activation in crGN. Activated p38MAPK co-localised with α, β and γ isoforms in podocytes and crescents, while leucocytes showed mainly p38MAPKα activation. In a human podocyte cell line mRNA and protein of all four p38MAPK isoforms was expressed but only p38MAPKα was activated upon challenge with TNF. Conclusions: This study shows selective p38MAPK isoform expression and activation in crGN. Podocytes and podocyte-induce crescent formation is the main source of p38MAPK activation in crGN. TNF is a potent and selective activator of the α-isoform in podocytes, which therefore appears as a main contributor to proinflammatory signalling in the glomerulum of crGN.